A Blood-Borne PDGF/VEGF-like Ligand Initiates Wound-Induced Epidermal Cell Migration in Drosophila Larvae. - Wu, Y.; Brock, A.R.; Wang, Y.; Fujitani, K.; Ueda, R.; Galko, M.J. (Current Biology, 2009)
Epidermal cell migration is critical for restoration of tissue structure and function after damage. However, the mechanisms by which differentiated cells neighboring the wound sense the wound and assume a motile phenotype remain unclear. Here, we show that Pvr, a receptor tyrosine kinase (RTK) related to platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) receptors, and one of its ligands, Pvf1, are required for epidermal wound closure. Morphological comparison of wound-edge cells lacking Pvr or the Jun N-terminal kinase (JNK) signaling pathway previously implicated in larval wound closure suggests that Pvr signaling leads wound-margin epidermal cells to extend actin-based cell processes into the wound gap while JNK mediates transient dedifferentiation of cells at the wound margin. Genetic epistasis experiments reinforce the conclusion that the JNK and Pvr signaling pathways act in parallel. Tissue-specific knockdown and rescue experiments suggest that epidermally derived Pvf1 may be sequestered in the blood and that tissue damage exposes blood-borne Pvf1 to Pvr receptors on wound-edge epidermal cells and initiates the extension of cell processes into the wound gap. These results uncover a novel mechanism of sensing tissue damage and suggest that PDGF/VEGF ligands and receptors may play a conserved autocrine role in epidermal wound closure.